2018
DOI: 10.32596/ejcm.18.00311
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Short and Prolonged ACT Groups During Cardiopulmonary Bypass about Postoperative Drainage and Blood Transfusion

Abstract: Coagulation cascade starts with exsanguination or any contact of blood with an extracorporeal surface (1-5). Since invention of heparin molecule in 1916, it has been an essential application for cardiopulmonary bypass (CPB). Nowadays during CPB we have been using Activated Clotting Time (ACT) test because it results quicker than other laboratory tests to evaluate anticoagulation of heparin. (6-10) During CPB, high anticoagulation levels would result with unexpected high rate non-surgical bleeding. However, low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…3,5 There are studies that show reduced incidence of perioperative bleeding, when Heparin administration is monitored with ACT. 8,9 Lower ACT values are associated with high risk of thrombus formation in the extra-corporeal circuit, and higher values may lead to excessive perioperative bleeding. 9,10 It is therefore recommended to achieve safe target ACT, before CPB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5 There are studies that show reduced incidence of perioperative bleeding, when Heparin administration is monitored with ACT. 8,9 Lower ACT values are associated with high risk of thrombus formation in the extra-corporeal circuit, and higher values may lead to excessive perioperative bleeding. 9,10 It is therefore recommended to achieve safe target ACT, before CPB.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Lower ACT values are associated with high risk of thrombus formation in the extra-corporeal circuit, and higher values may lead to excessive perioperative bleeding. 9,10 It is therefore recommended to achieve safe target ACT, before CPB.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, greater amounts of fresh frozen plasma and platelet concentrate were required for group B than for group A (p=0.014 and p=0.021, respectively). Ozkan et al [12] retrospectively compared patients who underwent open heart surgery whose ACTs were 400-650 seconds with those with ACTs of 650 seconds or higher during CPB. They reported that drainage on postoperative day 1 (p=0.000), the postoperative blood transfusion amount (p=0.010), and intensive care duration (p=0.0015) were more favorable in the group with an ACT range during CPB of 400-650 seconds.…”
Section: Discussionmentioning
confidence: 99%